2018
DOI: 10.1016/j.bandl.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual and linguistic narrative comprehension in autism spectrum disorders: Neural evidence for modality-independent impairments

Abstract: Individuals with autism spectrum disorders (ASD) have notable language difficulties, including with understanding narratives. However, most narrative comprehension studies have used written or spoken narratives, making it unclear whether narrative difficulties stem from language impairments or more global impairments in the kinds of general cognitive processes (such as understanding meaning and structural sequencing) that are involved in narrative comprehension. Using event-related potentials (ERPs), we direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 88 publications
(198 reference statements)
7
39
0
Order By: Relevance
“…Furthermore, visual narrative sequences can modulate the N400 effect to words that replace Peak panels (Manfredi, Cohn, & Kutas, ), suggesting cross‐modal semantic resources. In addition, attenuation of N400 effects has been shown to both visual and verbal narratives in individuals with autism compared to neurotypical controls, implicating similar processing mechanisms across modalities (Coderre et al., ).…”
Section: Further Implicationsmentioning
confidence: 99%
“…Furthermore, visual narrative sequences can modulate the N400 effect to words that replace Peak panels (Manfredi, Cohn, & Kutas, ), suggesting cross‐modal semantic resources. In addition, attenuation of N400 effects has been shown to both visual and verbal narratives in individuals with autism compared to neurotypical controls, implicating similar processing mechanisms across modalities (Coderre et al., ).…”
Section: Further Implicationsmentioning
confidence: 99%
“…Children with ASD also provide shorter narrations of picture stories than typically developing children (Tager-Flusberg, 1995). Finally, an ERP study found that semantic processing (the N400) was attenuated for (2016) AccuracyNarrative structure Greater tolerance of incongruity for greater fluency Cohn et al (2016) Ratings Morphological familiarity and interpretations Less tolerance of incongruity for greater fluency Bateman et al (2018) Eye movements Layout More fluency associated with more consistent reading paths across panels Kirtley et al (2018) Eye movements Text-image relationships Larger saccades within panels for greater fluency incongruities in both verbal and visual narratives for individuals with ASD compared to neurotypical controls (Coderre et al, 2018).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…In a study using electroencephalography (EEG), Coderre et al () examined visual narrative comprehension in adults with ASD and NT controls. Narratives ended in a panel that was either semantically congruent or incongruent with the preceding story.…”
Section: Tests Of the Visual Ease Assumptionmentioning
confidence: 99%